Mechanism of immunoprotective effects of curcumin in DLM-induced thymic apoptosis and altered immune function: an in silico and in vitro study. (2nd November 2015) - Kumar, Anoop; Sasmal, Dinakar; Jadav, Surender Singh; Sharma, Neelima
Abstract: Curcumin, a main component of Curcuma Longa Linn, is a plant polyphenol used as an immune-enhancer in the Indian system of traditional medicine. However, its underlying mechanism of immune-protection remains unknown. The present study is designed to delineate the role of curcumin in deltamethrin (DLM)-induced thymocyte apoptosis and altered immune functions. In silico studies revealed that curcumin has a strong binding affinity toward CD4 and CD8 receptors. DLM (25 µM) induces thymocytes apoptosis through oxidative stress and caspase-dependent pathways. Various concentrations of curcumin (1, 10 and 50 µg/ml), when added along with DLM, caused a concentration- and time-related amelioration in apoptogenic signaling pathways induced by DLM. Inhibition of DLM-induced reactive oxygen species production, replenishment of glutathione and suppression of caspase activities by curcumin may thus be responsible for the suppression of downstream cascade of events, i.e. apoptosis, phenotypic changes and altered cytokine release. Thus, this study clearly demonstrates that the mechanism of immunoprotection of curcumin in DLM-induced thymic apoptosis includes inhibition of oxidative stress and caspase-dependent pathways underlying apoptosis.